2020
DOI: 10.1037/adb0000580
|View full text |Cite
|
Sign up to set email alerts
|

Does alcohol cue inhibitory control training survive a context shift?

Abstract: This is a repository copy of Does alcohol cue inhibitory control training survive a context shift?.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
(122 reference statements)
1
4
1
Order By: Relevance
“…Regarding the effects of ICTs, our results indicate a lack of alcohol-specific training effects on any of the behavioral data. This null result diverge from several studies [55,88,89] but echoes recent data showing no effects of ICT on alcohol consumed in the context of training (lab-based), or in another context (semi-naturalistic bar), nor on inhibitory control processes, or on alcohol cueinhibition associations, or in alcohol value [58]. Our finding was also in line with broader literature on cognitive-bias-modification interventions showing weak and inconsistent effects on substance use [52,53] (but see Ref.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Regarding the effects of ICTs, our results indicate a lack of alcohol-specific training effects on any of the behavioral data. This null result diverge from several studies [55,88,89] but echoes recent data showing no effects of ICT on alcohol consumed in the context of training (lab-based), or in another context (semi-naturalistic bar), nor on inhibitory control processes, or on alcohol cueinhibition associations, or in alcohol value [58]. Our finding was also in line with broader literature on cognitive-bias-modification interventions showing weak and inconsistent effects on substance use [52,53] (but see Ref.…”
Section: Discussionsupporting
confidence: 80%
“…Another example of behavioral intervention is an alcohol adaptation of Inhibitory Control Training (ICT), which involves training participants to respond (i.e., press a key) to neutral stimuli and withdraw their response when alcoholrelated content is displayed [55]. A single session of alcohol ICT led to a reduction in alcohol consumption ad libitum among heavy social drinkers in the laboratory, but this reduction was short-lived and easily abolished by a context shift [55e57], which explains why the clinical relevance of ICT used in monotherapy seems limited [58]. Regarding the mechanisms of action of ICT, systematically matching a No-Go response with a motivational content has the potential to improve top-down inhibitory control [59], devaluate motivational cues (i.e., to reduce its positive valence) [60,61], or reinforce automatic cue/stop associations (i.e., associative inhibition) [57,61].…”
Section: Introductionmentioning
confidence: 99%
“…This may suggest that while the DLPFC appears to modulate the extent to which individuals can exert control over prepotent responses, this capacity does not appear to be directly related to drinking behaviour. This contrasts with early suggestions by Field et al (2010) but appears to be consistent with a growing body of more recent contributions (Christiansen et al, 2013;Jones et al, 2018;Jones et al, 2020;McNeill et al, 2018). Present (null) findings therefore appear to undermine further the notion of a causal link between inhibition impairments and loss of volitional control over actual beverage alcohol consumption and therefore may be more consistent with theoretical models that view inhibitory control as a more multifaceted construct that is embedded within wider cognitive processing networks (Verbruggen, 2016).…”
Section: Discussioncontrasting
confidence: 64%
“…Finally, adapting the task to the drinking behavior may increase the participants’ compliance. Previous studies using extended trainings are characterized by using multiple similar sessions (e.g., Jones et al, 2020 ; Scholten et al, 2021 ). However, individual adaptation of the difficulty may be useful to promote an overall training difficulty of moderate level (Benikos et al, 2013 ) and is therefore an important improvement for previous training paradigms (Peckham & Johnson, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…None of the previous studies investigating an alcohol-related GNG training paradigm (Di Lemma & Field, 2017 ; Houben et al, 2011 , 2012 ; Kilwein et al, 2018 ) have systematically investigated the performance in withholding motor responses as outcome of interest. Even though Strickland et al ( 2019 ) found an improved withholding performance after a 14-session training in individuals with Alcohol Use Disorder, they did not compare the withholding performance to their control groups (see also Jones et al, 2020 ). Only in smokers, Adams et al ( 2017 ) investigated GNG performance, but found no effect.…”
Section: Introductionmentioning
confidence: 99%